1997
DOI: 10.33584/jnzg.1997.59.2248
|View full text |Cite
|
Sign up to set email alerts
|

Annual and hybrid ryegrass cultivars in New Zealand

Abstract: Results are presented for 16 National Forage Variety Trials of annual and short-term hybrid ryegrass cultivars conducted in Waikato, Taranaki, Manawatu, Canterbury and Southland. In all, 30 cultivars (17 named, 13 experimental) were included. Cultivar effects were significant in all seasons, and for the annual totals. Cultivar differences were greatest in summer. Spring production accounted for over 40% of annual totals and summer production less than 20%, but it was summer production that was more clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Advances in perennial ryegrass breeding within New Zealand have taken place on many fronts, including yield, seasonal growth, disease resistance, endophytes, flowering behaviour and development of tetraploids. Estimates of the genetic progress for annual yield are between 0.25 and 1.5% per year (Easton et al 1997, 2001, Woodfield & Easton 2004, a rate comparable with white clover and other crops. However, in practice cultivars are used in mixtures with white clover and any genetic increase in the ryegrass component may partially suppress clovers to limit increases in overall pasture yields.…”
Section: Genetic Progress and Breedingmentioning
confidence: 94%
“…Advances in perennial ryegrass breeding within New Zealand have taken place on many fronts, including yield, seasonal growth, disease resistance, endophytes, flowering behaviour and development of tetraploids. Estimates of the genetic progress for annual yield are between 0.25 and 1.5% per year (Easton et al 1997, 2001, Woodfield & Easton 2004, a rate comparable with white clover and other crops. However, in practice cultivars are used in mixtures with white clover and any genetic increase in the ryegrass component may partially suppress clovers to limit increases in overall pasture yields.…”
Section: Genetic Progress and Breedingmentioning
confidence: 94%
“…The 1.18% increase in annual ryegrass annual yield was almost double that reported for annual ryegrass (0.5% per year) in Europe (van Wijk & Reheul 1991). Further evidence of genetic improvement in annual ryegrass yield can be observed from the performance of G. Moata, the control cultivar used by Easton et al (1997). G. Moata was consistently amongst the poorest performing cultivars for seasonal and annual yield (Easton et al 1997), however, when it was first released it yielded 15-20% better than the next best annual ryegrass (Rumball & Armstrong 1975).…”
Section: Annual Forage Yieldmentioning
confidence: 97%
“…Genetic improvement in seasonal yield of annual ryegrass (derived from Easton et al (1997) data; 11 cultivars with yield from between 7 and 16 trials). and in the associated endophyte strain (Westwood & Norriss 1999).…”
Section: Tablementioning
confidence: 99%
“…Genetic improvement of pasture plants has been pursued for over 85 years (Wratt & Smith 1983), with documented gains in dry matter (DM) production, disease resistance and forage quality (Corkill 1949;Kerr 1987;Easton et al 1989;Easton et al 1997;Woodfield 1999;Easton et al 2001). Genetic gains averaging around 0.5% per year for total annual DM yield (Lee et al 2012) have been demonstrated through small plot trials (Kerr 1987;Pennell et al 1990;Easton et al 2001;Hume et al 2007).…”
Section: Introductionmentioning
confidence: 99%